Transcript of World Bank Group President David Malpass at Spring Meetings 2022 Opening Press Conference - Malpass, David (World Bank, Washington, DC, 2022)
These remarks were delivered by World Bank Group President David Malpass at Spring Meetings 2022 Opening Press Conference on April 20, 2022. He said that the World Bank Group has been acting fast in the face of the crises: first the COVID-19 surge financing in over the last two years, which was one of the fastest and largest in our history; and now putting money into Ukraine and have moved quickly both to commitments and disbursements, including nearly 1.5 billion dollars that he announced in Poland last week. He mentioned that the World Bank is working actively on climate, through their Climate Change Action Plan and the formation of Country Climate and Development Reports (CCDRs), which will identify the high priority items country by country, in their efforts to mitigate and to adapt to climate change. He insisted that one of the solutions for the world is to recognize that markets are forward looking. He mentioned that as interest rates rise, the debt pressures are mounting on developing countries, and we need to move urgently towards solutions. He hopes and expects that many countries will step forward with individual solutions to alleviate the food crisis and the fertilizer crisis. He explained the efforts to support people within Mexico, and the World Bank is interested in working with governmental entities on that. He spoke about Nigeria has huge opportunity because of its natural resources and because of its people, and could see its growth accelerate with improvements in policy. He insisted that there needs to be substantial investment in the backbone of the global electricity system in terms of baseload and grid in order to get through to the other side of this energy crisis. He did a joint statement with IMF, with WTO, and with the World Food Program late the week before stating these views, that it's important that the world increase supply and not close markets, not fragment markets, as we move through this crisis. He hopes, as we look at the resolution to the current crisis, one of the key steps will be for the central banks and the fiscal authorities to use their tools to improve the allocation, to allow an allocation of capital that goes more towards small businesses, new businesses, and developing countries.